Gallbladder Carcinoma Associated with Anomalous Pancreaticobiliary Duct Junction - Chang Moo Kang; Kyung Sik Kim; Jin Sub Choi; Woo Jung Lee; Byong Ro Kim (Canadian Journal of Gastroenterology)
BACKGROUND: Anomalous pancreaticobiliary ductal junction (APBDJ) is believed to be one of the risk factors for gallbladder carcinoma. The present study aims to delineate the gallbladder carcinoma characteristics associated with APBDJ.